2013
DOI: 10.1371/journal.pone.0076960
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Deep Intronic SNP rs13438494 in Intron 24 of PCLO Gene

Abstract: The single nucleotide polymorphism (SNP) rs13438494 in intron 24 of PCLO was significantly associated with bipolar disorder in a meta-analysis of genome-wide association studies. In this study, we performed functional minigene analysis and bioinformatics prediction of splicing regulatory sequences to characterize the deep intronic SNP rs13438494. We constructed minigenes with A and C alleles containing exon 24, intron 24, and exon 25 of PCLO to assess the genetic effect of rs13438494 on splicing. We found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 21 publications
1
32
0
Order By: Relevance
“…The polymorphisms selected for this study are located within the introns of the TIMP2 gene and do not affect the protein structure. They may indirectly affect the level of transcription by altering the structure of the DNA‐binding site of regulatory proteins or the effect on mRNA stability or lead to DNA‐histone binding strength alternations, but such relationships have not yet been described in the literature for any of the assessed SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…The polymorphisms selected for this study are located within the introns of the TIMP2 gene and do not affect the protein structure. They may indirectly affect the level of transcription by altering the structure of the DNA‐binding site of regulatory proteins or the effect on mRNA stability or lead to DNA‐histone binding strength alternations, but such relationships have not yet been described in the literature for any of the assessed SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the SNP–SNP interactions showed a strong interaction between these SNPs regarding susceptibility to lung cancer. Several studies provided increasing evidence to support that intronic SNPs confer susceptibilities by affecting the binding of transcription factor binds and/or RNA splicing (Seo et al, ; D. Wang & Sadee, ; Zhao et al, ). However, the mechanisms on the biological function of these SNPs in IL1R2 are unknown and need more functional studies to explore.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al reported that the variation (T4127G) in intron2 of CYP3A4 exists in the human liver, which could significantly decreases the hepatic microsomal testosterone 6-hydroxylase activity of cytochrome P450, family 3, subfamily A (CYP3A) [25] . Seo et al [26] demonstrated that intronic SNP rs13438494 alters splicing efficient creating or disrupting a splicing motif, which may ultimately result in bipolar disorder in affected people. In Holsteins, Wang et al [27] detected a SNP (c. 1033 + 2184 C>T) in intron 8 of CD46 molecule (CD46), which results in CD46-transcript GUI, WANG, JIA ZHANG, CHEN, HOU [28] showed that a point variation in intron1 (A3481C) of fatty acid binding protein 4, adipocyte (A-FABP) had strong effect on intramuscular fat content in Junmu No.…”
Section: Discussionmentioning
confidence: 99%